Luleås Norra hamnfjärd och stränder : Förutsättningar, potential och förslag - Johansson Klang, Erik (2013)
During the 16th century the town of Luleå moved from its first location Gammelstad to the Northern harbour “Norra hamn” because of the need of a harbour. “Norra hamn” was the centre for trading for a long time as the harbour kept on growing in importance. With the plans for expansions of the iron industry, by a new steelworks in the late 1970s the roads demanded a larger capacity to get all the new people to work. Many of the roads in and around the city was therefore broadened, among these were the roads around the Northern harbour. The new steelworks was never built and there was no increase in traffic either, but the roads are still to this day very largely dimensioned. Due to this, the activity around the Northern harbour is now limited to function as one of Luleå´s biggest routes for vehicle transportation. Today the area around the Northern harbour mainly consists of roads, with “Bodenvägen” in the north with 4 lanes and 20 meters in width. Along the shoreline runs a walking path which is only separated from the traffic by an elevated curb. “Bodenvägen” ends at the roundabout near “Kulturens hus” where the traffic is lead west along the shoreline on to “Skeppsbrogatan”, also with 4 lanes and 20 meters in width. This traffic situation creates great barrier effects which separate the Northern harbour from the rest of the city centre. This further leads to cars and vehicles being prioritised over pedestrians in regards of the space closest to the shorelines of the Northern harbour. This master thesis will, with the methods for analysing smaller urban spaces by Jan Gehl, Kevin Lynch´s methods for visual analysis and the method of Space syntax for analysing the integration between the urban spaces in the city, investigate the existing conditions of the Northern harbour and it´s future potential to once again function as a public place in the city. The purpose of this master thesis is to show that if we can create better spaces and conditions for city life, then the situation of today offers, we can also make a ...